Evaluasi Strategi Turnaround SBU Pos Admail PT Pos Indonesia - , Nurlia Hikmah; , Dr. Amin Wibowo, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The process of turnaround or reorganization of PT Pos Indonesia (Persero) which lasted from 2007 until today have implications for the survival of one of its business unit, SBU Pos Admail. Internal and external factors that affect the corporate business plan led to the formation of PT Admailpos, a subsidiary Pos Indonesia came from SBU Pos Admail cannot be realized. At the stage of corporate reorganization in 2012, SBU Pos Admail is no longer as a business unit of the company, not even developed into a subsidiary, but it will become an area organization that has a limited within the authority and daily operations management. This study aims to gain an overview and understanding of the condition of the SBU Pos Admail performance in the period 20XX-20XX. Performace evaluation seen in the financial perspective by comparing business unit target in RKAP with the realization report of the business unit, which is supported by the calculation of return on investment (ROI) business unit as a profit center. The next stage of the analysis is to identify the level of fit between the business unit and the corporate through a method that uses Corporate Parenting Framework concept (Campbell, Goold, Alexander, 1995). Assessment conducted within the framework of this parenting is at the fit level between the parent's company's skill and business needs. If both of these elements show a high level of compliance, it will create an uneven advantage, but if it show the low level of compliance would damage the value of the business. In this study, the framework is used as the basis for answering the closing of Pos Admail business unit cases.